Enhancement Of Mechanical And Microstructural Properties Of Concrete Using Microcrystalline Cellulose And Fly Ash - Thomas, Christopher Edwin; Saravanan, J. (Journal of Neonatal Surgery, 2025)
This study looks into the impact of using Microcrystalline Cellulose (MCC) and Class F fly ash (FA) as partial cement substitutes on the fresh, mechanical, and microstructural properties of concrete. Using the ACI mix design approach, several mix proportions were created, and their performance was assessed using slump tests, compressive strength tests, stress-strain behavior, and Scanning Electron Microscopy. The results showed that the addition of FA increased workability due to its spherical particle morphology, whilst MCC significantly lowered slump values due to its fibrous character. Compressive strength results showed that the optimum mix (M2-cement +0.6% of MCC and 15% of FA) containing both MCC and fly ash achieved higher strength than the conventional mix (M0- concrete with admixtures), suggesting enhanced cementitious reactions and better matrix densification. The stress-strain analysis confirmed increased ductility and energy absorption in the M2 mix. SEM images further revealed a denser, less porous microstructure in the modified mix, with fewer cracks and more compact hydration products. Overall, the study demonstrates that the combined use of MCC and fly ash not only improves concrete performance but also supports sustainable construction practices by reducing cement consumption and utilizing industrial by-products effectively.